Implementation of Inclusive Character Education in Fostering Students' Tolerance - Dewi Luthfiyah; M. Jamhuri; M. Anang Sholikhuddin (Journal of Contemporary Islamic Education, 2026)
The internalization of tolerance values in Islamic education has not yet been optimally implemented, as it remains predominantly focused on cognitive understanding rather than being reflected in students’ actual behavior. Furthermore, the increasing diversity of students’ social and cultural backgrounds requires an inclusive, contextual, and transformative educational approach to cultivate tolerance and foster a harmonious learning environment. This study aims to analyze the implementation of inclusive character education in fostering students’ tolerant attitudes at MTs Favorit Darut Taqwa Mojokerto within the context of Islamic education. A qualitative approach with a case study design was employed. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using an interactive data analysis model. The findings reveal that the implementation of inclusive character education creates an open, participatory, and non-discriminatory learning environment that encourages positive social interaction among students from diverse backgrounds. Collaborative learning strategies, including group discussions and heterogeneous group formation, effectively promote empathy, respect for differences, cooperation, and mutual understanding among students. The findings further indicate that tolerance is more effectively internalized through sustained social interaction and habituation than through formal classroom instruction alone. This study concludes that inclusive character education plays a strategic role in strengthening students’ social character and cultivating a tolerant, inclusive, and harmonious educational environment.